Observer-based attitude controller for lifting re-entry vehicle with non-minimum phase property. (4th May 2017) - Nie, Wenming; Li, Huifeng; Zhang, Ran
This article concentrates on the attitude control problem for the lifting re-entry vehicle with non-minimum phase property. A novel attitude control method is proposed for this kind of lifting re-entry vehicle without assuming the internal dynamics to be measurable. First, an internal dynamics extended state observer is developed to deal with the unmeasurable problem of the internal dynamics. And then, the control scheme which adopts output feedback method is proposed by modifying the traditional output redefinition technique with internal dynamics extended state observer. This control scheme only requires the system output to be measurable, and it can still stabilize the unstable internal dynamics and track attitude commands. Besides, because of the inherent property of extended state observer in rejecting uncertainties and disturbances, the control precision of the proposed controller is higher than the controller designed with traditional output redefinition technique. Finally, the effectiveness and robustness of the proposed attitude controller are demonstrated by the simulation results.